Regulation of Fatty Acid Metabolism and Inhibition of Colorectal Cancer Progression by Erchen Decoction. (10th April 2023) - Liao, Linghong; Zhang, Fei; Zhuo, Zewei; Huang, Chengbao; Zhang, Xiaofang; Liu, Ruifang; Gao, Bizhen; Ding, Shanshan
Abstract : Erchen decoction (ECD) is a traditional Chinese prescription widely used in the treatment of various diseases such as obesity, fatty liver, diabetes, and hypertension. In this study, we investigated the effect of ECD on fatty acid metabolism in a colorectal cancer (CRC) mouse model fed a high-fat (HF) diet. The HF-CRC mouse model was established by azoxymethane (AOM)/dextran sulphate sodium (DSS) combined with a high-fat diet. Mice were then gavaged with ECD. Change in the body weight was recorded every two weeks for 26 weeks. Changes in blood glucose (GLU), total cholesterol (TC), total triglycerides (TG), and C-reactive protein (CRP) were measured. Colorectal tissues were collected to observe changes in colorectal length and tumorigenesis. Hematoxylin-eosin (HE) staining and immunohistochemical staining were performed to observe changes in intestinal structure and inflammatory markers. Fatty acids and the expression of related genes in colorectal tissues were also studied. ECD gavage inhibited HF-induced weight gain. CRC induction and HF diet intake resulted in increased GLU, TC, TG, and CRP, where ECD gavage reduced these elevated indicators. ECD gavage also increased colorectal length and inhibited tumorigenesis. HE staining revealed that ECD gavage suppressed inflammatory infiltration of colorectal tissues. ECD gavage suppressed the fatty acid metabolism abnormalities caused by HF-CRC in colorectal tissues. Consistently, ECD gavage lowered ACSL4, ACSL1, CPT1A, and FASN levels in colorectal tissues. Conclusions . ECD inhibited HF-CRC progression through the regulation of fatty acid metabolism.